Split domination number of divisible dominating graphs. (19th May 2021) - Amutha, S.; Suriya Prabha, K.; Anbazhagan, N.; Shanthi, P.
Abstract: A graph G is a divisible dominating graph if the vertices are labeled with positive integers d and n except 0, such that the vertex labeled with n is adjacent to the vertex named with d if and only if d | n . In this paper, we introduce the concept of some special classes of divisible dominating graphs and we investigate the split domination number of such graphs.